PREGNANCY OUTCOME IN PATIENT WITH ADULT ONSET STILL’S DISEASE-A RARE CASE REPORT - SHASHIKALA .G.; SUMATHI.K.; ANURADHA.C. (International Journal of Pharma and Bio Sciences, 2013)
Still’s disease is an arthritis of adult onset, rare in general population, even rarer in pregnancy, and often associated with flare-up and relapses during pregnancy and postpartum period. The following is a rare case of pregnancy in Still’s disease with uneventfull outcome.